Effect of tax policies on tax compliance and the moderating role of gender: evidence from the SMEs in Zimbabwe - Wilbert Manyanga; James Kanyepe; Asphat Muposhi; Tendai Manyanga; Augustine Torayi Mataba (Cogent Business & Management)
The paper examined the effect of tax policies on tax compliance and the moderating role of gender. A positivist research philosophy and quantitative research strategy were adopted. A cross-sectional survey design was used to collect data from 220 SMEs owners and representatives using a structured interviewer-administered questionnaire. SMEs owners and representatives were selected by randomly intercepting them at break time and lunch time during SMEs conferences and workshops in Harare, Zimbabwe. Structural equation modelling was used to test research hypotheses. The study established that low tax penalties, low tax rates and fairness and equity of a tax system positively influence tax compliance. Furthermore, the study established that gender moderates the effect of low tax penalties, low tax rates and fairness and equity of a tax system on tax compliance. Results imply that reasonable tax penalty and tax rates accompanied by a fair and equity tax system play an imperative role in increasing tax compliance and revenue for the nation. Also, the results imply that gender plays a moderating role in influencing tax compliance. Policymakers should consider low tax rates, low penalties and fairness and equity in the tax system to improve tax compliance by SMEs. Also, policymakers should consider ways to ensure that all taxpayers are tax compliant, despite their gender. The tax authorities may use deterrence letters or letters of demand to ensure males are compliant.